Konteks Preservasi Pengetahuan pada Preservasi Permainan Tradisional di Perpustakaan Umum dan Arsip Kabupaten Pacitan - Dedy Dwi Putra (LIBTECH: LIBRARY AND INFORMATION SCIENCE JOURNAL, 2022)
Traditional games, as part of Indonesian culture, have important values to be preserved. It becomes meaningful because traditional games have heritage and knowledge value that is very valuable for human life. Knowledge in human’s everyday life occupies an important and strategic position that has a major impact on the process of human activities. It’s rationalization becomes a foundation to save knowledge through the preservation of knowledge. Preservation of traditional games as part of knowledge preservation is an important aspect to be explored further. This study seeks to explore aspects of knowledge preservation value that embedded in preservation of traditional games. This study uses a qualitative approach with data collection through interview, observation and direct involvement in preservation of traditional games. The analytical approach used in this paper is a knowledge preservation strategy. The results showed that the context of knowledge preservation in the preservation of traditional games in the Public Library and Archive of Pacitan was manifested in various activities. From the preservation of these traditional games, there are several knowledge preservation perspectives, including the archival perspective, human resource and organizational learning perspective, project based perspective, and business process re-engineering each of which is manifested in the preservation of traditional games. Keyword: knowledge preservation, public library, traditional games